An Examination of Current Leadership Practices in Early Childhood and Early Childhood Special Education: A Mixed Methods Study. Issue 4 (19th May 2022) - Movahedazarhouligh, Sara; Banerjee, Rashida; Luckner, John
ABSTRACT: Rh Findings : Effective leadership is one necessary element of achieving high quality in early childhood (EC) and early childhood special education (ECSE) programs. To date, little leadership literature and research are available for EC/ECSE professionals. Using a mixed-methods research approach, this study investigated local leadership practices in one western state in the United States. A hundred forty-three leaders from state or federally funded EC/ECSE programs participated in an online survey (phase I). Four state-level EC/ECSE leaders participated in individual interviews (phase II). The findings of phase I provided valuable insight into local leadership implementation status, implementation challenges, and professional development needs and were well-aligned with the phase II state-level leaders' perceptions. Prce or Policy : The findings suggest that the local leaders need more targeted support opportunities to improve as a leader than a manager. The need for EC/ECSE leadership licensure, endorsement/certification, specific leadership performance standards, and credentials are discussed.